Dead mountain - Preston, Douglas J.; Child, Lincoln (Preston, Douglas J. Nora Kelly novel, 2023)
"In 2008, nine mountaineers failed to return from a winter backpacking trip in the New Mexico mountains. At their final campsite, searchers found a bizarre scene: something had appeared at the door of their tent so terrifying that it impelled them to slash their way out and flee barefoot to certain death in a blizzard. Despite a diligent search, only six bodies were found, two violently crushed and inexplicably missing their eyes. The case, given the code name "Dead Mountain" by the FBI, was never solved. Now, two more bodies from the lost expedition are unexpectedly discovered in a cave, one a grisly suicide. Young FBI Agent Corrie Swanson teams up with archaeologist Nora Kelly to investigate what really happened on that fateful trip fifteen years ago--and to find the ninth victim. But their search awakens a long-slumbering evil, which pursues Corrie and Nora with a vengeance, determined to prevent the final missing corpse from ever coming to light"--